(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Obstructive sleep apnea (OSA) is a common sleep disorder caused by the collapse of the upper airway during sleep due to a shift of soft tissues. To optimise the treatment, one needs a better understanding of the patient-specific causes. For this purpose, flow measurements shall be executed with flexible phantoms. A first measurement campaign was carried out with a flexible stenosis phantom. To build this phantom a multipiece water-soluble casting mold was fabricated with additive manufacturing and used to cast the phantom with silicone. The quality of the phantom was tested with regard to the wall thickness using CT measurements.